Alternative Sources of Retirement Funding with Respect to Opportunities and Risks of Reverse Mortgage - Paduszyńska, Marta; Zbyszewski, Szymon (Journal of Finance and Financial Law, 2016)
Demographic transitions are becoming a crucial aspect of contemporary economies. This article presents main demographic changes and their influence on the social security system. The aim of this work is to show the importance of finding new commodities and services for the ageing society, in the light of contemporary socioeconomic challenges. Undoubtedly, reverse mortgage is the one such products. The article proves the core of reverse mortgage and points to opportunities it gives up against social needs.